Applied hierarchical modeling in ecology. analysis of distribution, abundance and species richness in R and BUGS /: analysis of distribution, abundance and species richness in R and BUGS. Prelude and static models : Volume 1, ([2016]) - Kéry, Marc; Royle, J. Andrew
No abstract available